Nebivolol compared with metoprolol for erectile function in males undergoing coronary artery bypass graft - Aldemir, Mustafa (Anatol J Cardiol, 2016)
OBJECTIVE: The aim of this study was to evaluate erectile function in males undergoing coronary artery bypass graft (CABG) while on two different adrenoceptor beta-blocker regimens, namely nebivolol and metoprolol. We hypothesize that the negative effects of cardiopulmonary bypass on erectile function may be possibly attenuated by preferring a vasodilating selective β(1)-blocker, nebivolol, to metoprolol as an anti-ischemic and antiarrhythmic agent in males undergoing CABG. METHODS: This randomized, double-blind, prospective clinical study was conducted in patients scheduled for CABG surgery between February 2012 and June 2014. A total of 60 consecutive patients who met inclusion criteria were randomized and divided into the following two groups: N group, which received 5 mg of nebivolol orally for 2 weeks before surgery plus 12 weeks after surgery or M group, which received 50 mg of metoprolol orally for the same period. All patients were evaluated by the erectile function domain of the International Index of Erectile Function-5 (IIEF-5) at the time of admission (before starting the beta-blocker) and 3 months after surgery. RESULTS: In the metoprolol group, the mean IIEF-5 score decreased significantly from a baseline of 15.2±5.8 to 12.9±5.8 (p<0.001), but in the nebivolol group, this difference was not significant (from a baseline 12.9±5.5 to 12.4±5.5, p=0.053). In all patients, the mean IIEF-5 score decreased significantly from a baseline of 14.0±5.7 to 12.6±5.6 (p<0.001). CONCLUSION: Although erectile function in males undergoing CABG surgery decreases when metoprolol is used, nebivolol exerts protective effects on erectile function against the disruptive effects of cardiopulmonary bypass in patients undergoing CABG.